2013
DOI: 10.1155/2013/875108
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Facial Palsy in Rapidly Progressive Course of Wegener’s Granulomatosis: A Case Report

Abstract: Introduction. Wegener's granulomatosis belongs to a group of systemic vasculitis diseases, which is characterized by necrotizing vasculitis and presence of granulomas. In a lot of cases, the first symptoms of the disease are observed in the head and neck region, but the bilateral facial nerve palsy occurs very rarely. Objective. The objective of our report was to describe the unusual course of Wegener's granulomatosis with the bilateral facial nerve paralysis, which subsided after application of steroids and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Occasionally, the progressive course of the disease may lead to bilateral facial palsy, which was observed in our patient. Bilateral facial palsy is an extremely rare finding [19]. In the review of 2856 patients with facial paralysis Lee et al reported only 2% of cases with bilateral involvement [20].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Occasionally, the progressive course of the disease may lead to bilateral facial palsy, which was observed in our patient. Bilateral facial palsy is an extremely rare finding [19]. In the review of 2856 patients with facial paralysis Lee et al reported only 2% of cases with bilateral involvement [20].…”
Section: Discussionmentioning
confidence: 99%
“…Many authors recommend conservative treatment, as it usually results in nerve function recovery, whereas surgery may increase the risk of additional nerve injury [14, 19]. However, unusual manifestation at the onset of the disease may delay the correct diagnosis and the suspicion of GPA only appears in the case of failure of conventional therapy or when additional symptoms from other organs occur.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations